Pengaruh Penggunaaan Digital Payment System dan Persepsi Masyarakat Muslim Terhadap Perilaku Konsumtif Masyarakat Muslim - Hidayanti, Fina; Laksamana, Rio; Putra, Windhu (STIE 'INDONESIA' Pontianak, 2024)
The use of digital payment systems has attracted attention as an effective and efficient way to facilitate financial transactions. This type of fintech allows financial transactions to be carried out online and offline using electronic devices. This study aims to identify the extent to which the use of digital payments affects the consumptive behavior of Muslim communities. The research method used in this study uses quantitative descriptive research methods. The population in this study is the Muslim community in Pontianak which amounted to 518,952 people. In this study there are ten (10) indicators, so it is ideal to use samples 7 times from the indicators, namely 70 samples or as many as 70 Muslim communities in Pontianak. The results showed that the use of digital payment systems and perceptions of Muslim communities can have a simultaneous and significant influence on consumer behavior